Does Farm and Processing Industry Structure Matter for Price Transmission? Some Evidence From Transition Countries: A Comparison of Dairy Sectors in Hungary and Poland - Zoltán Bakucs; Jan Fałkowski; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
Rapid and thorough changes have recently taken place in dairy supply chain in the whole Central and Eastern Europe. Growing concerns have been expressed that these changes may negatively affect farmers' relative position towards downstream industry, due to market power exercised by the latter. In response to this, the present paper aims to investigate the price transmission mechanism in two countries from the region, namely Poland and Hungary and contrast the results with dairy market organisations specific for these countries. Using cointegrated vector autoregression and controlling for potential structural breaks, it is shown that Polish milk prices, as opposed to Hungarian ones, are characterised by short- and long-term asymmetries. We discuss a number of potential explanations supporting the empirical results. We consider, among others, differences between the dairy chain structures and the role of FDI.
Keywords: Q13; D12; D4; 330; price transmission; dairy sector; Hungary; Poland; Milchverarbeitung; Lieferkette; Milchpreis; VAR-Modell; Polen; Ungarn